Post-enzymatic hydrolysis heat treatment as an essential unit operation for collagen solubilization from poultry by-products. (15th July 2022) - Kristoffersen, Kenneth Aase; Afseth, Nils Kristian; Böcker, Ulrike; Dankel, Katinka Riiser; Rønningen, Mats Aksnes; Lislelid, Andreas; Ofstad, Ragni; Lindberg, Diana; Wubshet, Sileshi Gizachew
Graphical abstract: Highlights: The role of thermal inactivation in collagen solubilization during EPH was studied. Two protases with very different mode of action towards collagen were included. 180 hydrolysates from different poultry by-products were produced. Heat assisted solubilization of partly hydrolyzed collagen was assessed. Sediment removal prior to thermal inactivation is a strategy to tailor hydrolysates. Abstract: Enzymatic protein hydrolysis (EPH) is an invaluable process to increase the value of food processing by-products. In the current work the aim was to study the role of standard thermal inactivation in collagen solubilization during EPH of poultry by-products. Hundred and eighty hydrolysates were produced using two proteases (stem Bromelain and Endocut-02) and two collagen-rich poultry by-products (turkey tendons and carcasses). Thermal inactivation was performed with and without the sediment to study the effect of heat on collagen solubilization. A large difference in molecular weight distribution profiles was observed when comparing hydrolysate time series of the two proteases. In addition, it was shown that 15 min heat treatment, conventionally used for inactivating proteases, is essential in solubilizing collagen fragments, which significantly contributes to increasing the protein yield of the entire process. The study thus demonstrated the possibility of producing tailored products of different quality by exploiting standard heat inactivation in EPH.